TREATMENT OF BRAFV600E POSITIVE ANAPLASTIC THYROID CARCINOMA: CASE REPORT - P. A. Nikiforovich; P. O. Rumiantsev; I. V. Sleptsov; T. V. Ustinova; K. Yu. Slashchuk; S. L. Vorobyev; S. S. Serzhenko; A. Yu. Abrosimov; A. V. Kudryavtseva; A. A. Semenov; R. A. Chernikov; A. A. Polyakov; et al. (Сибирский онкологический журнал)
Anaplastic thyroid cancer is one of the most aggressive and fatal human carcinomas. A significant experience in using various kinase inhibitors for anaplastic thyroid cancer therapy has been accumulated worldwide. The most encouraging results were obtained after using a combination of b-Raf and MEK kinase inhibitors (vemurafenib/dabrafenib and trametinib/cobimetinib, respectively) for the treatment of the unresectable BRAFV600E-positive anaplastic thyroid cancer. This drug combination makes it possible to perform surgery followed by chemoradiotherapy and other targeted therapies. Here we report a clinical case of anaplastic thyroid cancer in a 69-year-old woman, who was treated with neoadjuvant targeted therapy. The treatment was carried out on the basis of three medical institutions: the National Medical Research Radiological Centre (Moscow), the N.I. Pirogov Clinic of Advanced Medical Technologies (St. Petersburg) and the Endocrinology Research Center (Moscow). Since there is still no universal protocol for treating ATC patients, and only palliative therapy is used in most cases, we emphasized on diagnostic and treatment errors of this disease. Special attention was paid to the importance of using molecular diagnostics and modern medical imaging technologies.